On the exponential dichotomy of linear almost periodic pulse systems - Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For a linear almost periodic pulse system, we prove that the exponential dichotomy on a semiaxis implies the exponential dichotomy on the entire axis.